2005
DOI: 10.1577/t04-086.1
|View full text |Cite
|
Sign up to set email alerts
|

Brown Bullhead as an Indicator Species: Seasonal Movement Patterns and Home Ranges within the Anacostia River, Washington, D.C.

Abstract: Elevated liver and skin tumor prevalence has been reported in brown bullhead Ameiurus nebulosus from the tidal Anacostia River, Washington, D.C. Movement data are needed to effectively use tumor prevalence as an indicator of habitat quality. We used ultrasonic telemetry to verify the residency of 40 adult brown bullheads (250–310 mm total length) in the Anacostia River during summer 2000, spring 2001, and fall–winter 2001–2002. During summer (10 fish tagged), fish remained within 500 m of their capture–release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 38 publications
0
29
1
Order By: Relevance
“…Therefore, current conditions of liver tumor prevalence are very close to the delisting criterion of 5% under current guidance and within the range found in other AOCs following more active remedial activities. In fact, the current prevalence is very close to the 7 and 8% found in various reference sites in the Great Lakes [18]. Black River and Presque Isle are currently assigned a recovery stage listing status for the TOD BUI.…”
Section: Tumors In Brown Bullhead In the Buffalo Rivermentioning
confidence: 55%
See 1 more Smart Citation
“…Therefore, current conditions of liver tumor prevalence are very close to the delisting criterion of 5% under current guidance and within the range found in other AOCs following more active remedial activities. In fact, the current prevalence is very close to the 7 and 8% found in various reference sites in the Great Lakes [18]. Black River and Presque Isle are currently assigned a recovery stage listing status for the TOD BUI.…”
Section: Tumors In Brown Bullhead In the Buffalo Rivermentioning
confidence: 55%
“…There was no apparent relationship to fish length, and there was no upstream-downstream relationship, insofar as one neoplasm was found in each reach. Studies of the home range of brown bullhead suggest that the fish in the present study are indicative of exposures in their reaches [18].…”
Section: Neoplastic and Nonneoplastic Lesions In The Livermentioning
confidence: 58%
“…Previous studies indicate that channel catfish migrate downstream from tributaries to larger rivers during the autumn, move upstream from larger rivers to tributaries during the spring, and have relatively small home ranges within summer months (Dames et al 1989;Pellett et al 1998). Sakaris et al (2005) found that brown bullhead A. nebulosus travel upstream during the spring after an increase in water temperature and have relatively small home ranges (,0.5 km) during the summer. In our study, ictalurid fish displayed an upstream bias in movement direction during the late spring and early summer that was probably associated with spawning.…”
Section: Discussionmentioning
confidence: 92%
“…Beyond this statistical evidence, there is considerable biological evidence of intrapopulation heterogeneity in movement behaviour of salmonids (e.g. McLaughlin et al 1992;Bradford & Taylor 1997;Brännäs & Eriksson 1999;Steingrímsson & Grant 2003), as well as catfish (Sakaris, Jesien & Pinkney 2005), catostomids (Jeffres et al 2006), cyprinids (Skalski & Gilliam 2000), rivulines (Fraser et al 2001) and sculpins (Petty & Grossman 2004), and many of these studies suggest that individual differences are persistent. Simple models are appealing because they can describe dispersal properties with few parameters and do not require tailoring to system-specific detail.…”
Section: Discussionmentioning
confidence: 99%